An online resource for marine fungi - E. B.Gareth Jones (2019)
© 2019, School of Science. Index Fungorum, Species Fungorum and MycoBank are the key fungal nomenclature and taxonomic databases that can be sourced to find taxonomic details concerning fungi, while DNA sequence data can be sourced from the NCBI, EBI and UNITE databases. Nomenclature and ecological data on freshwater fungi can be accessed on http://fungi.life.illinois.edu/, while http://www.marinespecies.org/provides a comprehensive list of names of marine organisms, including information on their synonymy. Previous websites however have little information on marine fungi and their ecology, beside articles that deal with marine fungi, especially those published in the nineteenth and early twentieth centuries may not be accessible to those working in third world countries. To address this problem, a new website www.marinefungi.org was set up and is introduced in this paper. This website provides a search facility to genera of marine fungi, full species descriptions, key to species and illustrations, an up to date classification of all recorded marine fungi which includes all fungal groups (Ascomycota, Basidiomycota, Blastocladiomycota, Chytridiomycota, Mucoromycota and fungus-like organisms e.g. Thraustochytriales), and listing recent publications. Currently, 1257 species are listed in the marine fungi website (www.marinefungi.org), in 539 genera, 74 orders, 168 families, 20 classes and five phyla, with new taxa continuing to be described. The website has curators with specialist mycological expertise who help to provide update data on the classification of marine fungi. This article also reviews knowledge of marine fungi covering a wide range of topics: their higher classification, ecology and world distribution, role in energy transfer in the oceans, origin and new chemical structures. An updated classification of marine fungi is also included. We would like to invite all mycologists to contribute to this innovative website.